2017
DOI: 10.1038/srep42396
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced angiotensin II by the lactate-chymase-dependent mechanism mediates radioresistance of hypoxic tumor cells

Abstract: The renin-angiotensin system (RAS) is a principal determinant of arterial blood pressure and fluid and electrolyte balance. RAS component dysregulation was recently found in some malignancies and correlated with poor patient outcomes. However, the exact mechanism of local RAS activation in tumors is still unclear. Here, we find that the local angiotensin II predominantly exists in the hypoxic regions of tumor formed by nasopharyngeal carcinoma CNE2 cells and breast cancer MDA-MB-231 cells, where these tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…This evidence is the result of findings from the Lakatta s' group, using rat models, [62,63], and Šabovic's group [64], who propose administering combination of low-dose fluvastatin and valsartan, as anti-aging drugs. On the other hand, the expression and activity of Ang II, the angiotensin converting enzyme (ACE), the Ang II receptor AT1 receptor within the aorta wall, in particular, in the thickened intima in several species, including humans, are risen as the age progress [62][63][64][65][66][67][68][69][70][71]. Interestingly, also the chymase, another angiotensin-convertase, was found in the wall of aged aorta [69].…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence is the result of findings from the Lakatta s' group, using rat models, [62,63], and Šabovic's group [64], who propose administering combination of low-dose fluvastatin and valsartan, as anti-aging drugs. On the other hand, the expression and activity of Ang II, the angiotensin converting enzyme (ACE), the Ang II receptor AT1 receptor within the aorta wall, in particular, in the thickened intima in several species, including humans, are risen as the age progress [62][63][64][65][66][67][68][69][70][71]. Interestingly, also the chymase, another angiotensin-convertase, was found in the wall of aged aorta [69].…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 99%
“…On the other hand, the expression and activity of Ang II, the angiotensin converting enzyme (ACE), the Ang II receptor AT1 receptor within the aorta wall, in particular, in the thickened intima in several species, including humans, are risen as the age progress [62][63][64][65][66][67][68][69][70][71]. Interestingly, also the chymase, another angiotensin-convertase, was found in the wall of aged aorta [69]. Recently, two additional groups [70,71] evidenced that Ang II signaling cascades promote aorta remodeling by Fig.…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 99%
“…AGT,also called angiotensinogen,was knowned as precursor of the renin-angiotesin system.The human AGT gene ,which coded for a 485-amino acid protein,consisted of five extrons and four introns.Mature AGT protein contained 452 amino acid residues,which consisted of des(Ang I) AGT and angiotensin I(Ang I) ,an inactive decapeptide which is converted into Ang II [35] .Local Ang II in tumor environment(TME) produced by hypoxia-lactate-chymase-dependent mechanism was involved in immune escape and mediating radioresistance in tumor cells [36][37][38] .And augmented AGT and angiotesin-converting enzyme(ACE) released from apoptotic endothelial cells played a vital role in turning to Ang II to accelerate the progress of vascular remodeling [39] .It was demonstrated that human AGT inhibits endothelial cell proliferation and angiogenesis in vivo,and prevents tumor sinusoids from remodeling and anterialization,thus inhibits tumor progression [40,41] .Sun et al [42] also reported that high glucose promoted tumor proliferation by suppressing AGT expression.In this study,the downregulation of AGT represented that AGT expression decreased and the role of delaying tumor angiogenesis was weakened.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in the opinion of some authors, the HDAC of class I which is critically important for stimulating TGF-beta1-dependent renal fibrosis (Liu et al, 2013) it should be considered as the main target of such specific blockers. It is also suggested to apply the pharmacological correction of histone acetyl transferases (HATs) and histone deacetylases (HDACs) activity balance (Yuan et al, 2013).…”
Section: Mineralocorticoidsmentioning
confidence: 99%